THE EFFECT OF FISHBOWL STRATEGY ON STUDENTS’ READING COMPREHENSION AT THE ELEVENTH GRADE OF SMA MUHAMMADIYAH 18 SUNGGAL IN ACADEMIC YEAR 2019/ 2020 - Nurlela -; Efrini Panjaitan (Jurnal Serunai Bahasa Inggris, 2020)
This study aimed to find out whether using Fishbowl Strategy effects students’ reading skill of the 2019/2020 eleventh grade students At Muhammadiyah 18 Sunggal Senior High School. In this study, the writer used Fishbowl Strategy as the independent variable (X) and students’ reading skill as the dependent variable (Y), with the hypothesis: using Fishbowl Strategy significantly affects students’ reading skill of the 2019/2020 eleventh grade students of Muhammadiyah 18 Sunggal Senior High School. The population of this study was the 2019/2020 eleventh grade students of Muhammadiyah 18 Sunggal Senior High School which consisted of 76 students. The sample was taken by using cluster random sampling that consists of 76 students. Then, the sample was divided into two groups, the group taught by using Fishbowl Strategy was as the experimental group and the group taught without Fishbowl Strategy was as the control group. The writer used multiple choice tests as the instrument of collecting data. The data was analyzed by using t-test formula. Based on the data analysis, it was found that the value of t-observed (t0) was higher than the value of t-table, (tobserved = 4.75 > ttable = 1.666). Therefore, the hypothesis proposed by the writer was accepted. In the other words, using Fishbowl Strategy significantly affects the students’ reading skill of the 2019/2020 eleventh grade students At Muhammadiyah 18 Sunggal Senior High School.